2004
DOI: 10.1128/jvi.78.7.3244-3251.2004
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Coevolution of Baculoviruses and Their Insect Hosts

Abstract: If the relationships between baculoviruses and their insect hosts are subject to coevolution, this should lead to long-term evolutionary effects such as the specialization of these pathogens for their hosts. To test this hypothesis, a phylogeny of the Baculoviridae, including 39 viruses from hosts of the orders Lepidoptera, Diptera, and Hymenoptera, was reconstructed based on sequences from the genes lef-8 and ac22. The tree showed a clear division of the baculoviruses according to the order of their hosts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 51 publications
14
120
0
9
Order By: Relevance
“…Alk-exo gene clustering suggested that baculovirus clustered according to the different orders of insects. This demonstrates the existence of a co-evolutionary relationship between the virus and its host; similar results have been obtained from cluster analysis of the lef-8 gene and AC22 gene studied by Herniou et al (2004). Because the ubiquitin gene of baculovirus and hosts have very high homology, the evolutionary distance between the ubiquitin gene in the virus and insect hosts was not clear, both between and within groups.…”
Section: Discussionsupporting
confidence: 59%
“…Alk-exo gene clustering suggested that baculovirus clustered according to the different orders of insects. This demonstrates the existence of a co-evolutionary relationship between the virus and its host; similar results have been obtained from cluster analysis of the lef-8 gene and AC22 gene studied by Herniou et al (2004). Because the ubiquitin gene of baculovirus and hosts have very high homology, the evolutionary distance between the ubiquitin gene in the virus and insect hosts was not clear, both between and within groups.…”
Section: Discussionsupporting
confidence: 59%
“…The Aquarium Control and DOC samples contained a large fraction of sequences similar to ssDNA viruses from plants (white bars) such as geminiviruses and nanoviruses (39). Invertebrate infecting viruses (black bars) were also abundant (Ͼ60%) within the time zero library and were mostly similar to the baculoviruses and polydnaviruses, 2 viral families that predominantly infect arthropods (40)(41)(42). However, a caveat to this analysis is that the predicted host range is biased by the larger number of completed vertebrateassociated viral genomes.…”
Section: Coral-associated Viruses Infect a Range Of Hostsmentioning
confidence: 99%
“…For horses A1 and A2 ∼0.01% of sequence reads (2,954 and 3,522 reads, respectively) mapped to members of the Flaviviridae; 0.06% (9,116) of antitoxin 2 reads mapped to the same virus family. In addition to the abundance of Flaviviridae reads in each sample, horse A1 had a single read pair mapping to the Baculoviridae, a family of insect viruses (10), and another read pair derived from the Adenoviridae family, mapping to the region found in laboratory recombination vectors (11)(12)(13); horse A2 contained 80 read pairs deriving from a 298-nt contiguous region in pepper mild mottle virus, a plant virus from the Virgaviridae family. These reads likely represent artifactual contamination introduced during sample collection and library preparation.…”
Section: Viral Sequence Detection Leads To Assembly Of a Highly Divermentioning
confidence: 99%